2015
DOI: 10.1021/acsami.5b10132
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Property of Graphene Quantum Dots (Both Source Material and Bacterial Shape Matter)

Abstract: Whereas diverse graphene quantum dots (GQDs) with basal planes similar to those of graphene oxide sheets (i.e., GO-GQDs) lack antibacterial property, that prepared by rupturing C60 cage (i.e., C60-GQD) effectively kills Staphylococcus aureus, including its antibiotic-tolerant persisters, but not Bacillus subtilis, Escherichia coli, or Pseudomonas aeruginosa. The observed activity may correlate with a GQD's ability to disrupt bacterial cell envelop. Surface-Gaussian-curvature match between a GQD and a target ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 33 publications
1
86
0
Order By: Relevance
“…Along these lines, Akhavan and Ghaderi studied both the Gram-negative and -positive species in a pioneering work. [60] Interestingly, GQDs produced through the chemical rupture of C 60 cages exhibited antibacterial activity selectively against different S. aureus strains. Since the Gram-positive species have much thicker peptidoglycan layers compared to the Gram-negative ones, Akhavan and Ghaderi attributed their observation to the additional protection provided by the outer membrane structures found in Gram-negative cells.…”
Section: Influence Of Biotic Factors (Microorganisms)mentioning
confidence: 99%
See 3 more Smart Citations
“…Along these lines, Akhavan and Ghaderi studied both the Gram-negative and -positive species in a pioneering work. [60] Interestingly, GQDs produced through the chemical rupture of C 60 cages exhibited antibacterial activity selectively against different S. aureus strains. Since the Gram-positive species have much thicker peptidoglycan layers compared to the Gram-negative ones, Akhavan and Ghaderi attributed their observation to the additional protection provided by the outer membrane structures found in Gram-negative cells.…”
Section: Influence Of Biotic Factors (Microorganisms)mentioning
confidence: 99%
“…[92] Further, using AgNP-GQD hybrids for both the H 2 O 2 decomposition and the NIR-irradiated hyperthermia, they have achieved much more efficient bacterial inactivation. [60,[95][96][97] Moreover, we anticipate that the way GMs, in general, are combined with the bandage substrates can cause a notable change in end performance of antibacterial GM-textile composites. Particularly, we envision that the optimization of GQDs' properties may speed up the development of GQD-based antimicrobial wound bandages.…”
Section: Wound Bandages and Dressingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers demonstrated that, GQDs prepared by rupturing C 60 (C 60 ‐GQDs) killed more S. aureus than GQDs prepared from GO nanosheets (GO‐GQDs). GQDs seem to disrupt the envelopment of (and finally kill) cocci more readily than bacilli such as B. subtilis , E. coli , and P. aeruginosa …”
Section: Antibacterial Activities Of Single‐component Graphene and Itmentioning
confidence: 99%